Det Chinesiske Examens-Væsen - Bugge, Knud Eyvin (Grundtvig-studier, 2007)
Det “ Chinesiske” Examens-Væsen[The “ Chinese’’examination system]By K. E. Bugge Grundtvig's assaults on the educational practices of his time include attacks on “the Chinese examination system”. This surprising figure of speech is encountered in the initial sections of the third volume of his World History (1842), in which he deals inter alia with the first European sea-voyages to China in the early 16th century. In this context he describes the ponderous and exaggerated thoroughness in which the Chinese officials “examined” the Portuguese ships on their way to the harbour of Canton. Grundtvig, however, does not reveal any knowledge of the educational systems of China.According to Grundtvig’s footnotes his account is based on a comprehensive Portuguese publication, the Italian translation of which was accessible to him at the Royal Library in Copenhagen. The book is Fernando Lopes di Castagneda, Historia dell’ Indie Orientali (Venezia 1578). In this way we learn that Grundtvig was able to read Italian, a competence that of course was based on his supreme mastery of Latin.